En torno a la identificación de la ceca IKALE(N)SKEN (MLH A.95) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This  paper  provides  a  new  identification  of  the  nimt ikale(n)sken (MLH A.95).